Biogeochemical Processes in the Active Layer and Permafrost of a High Arctic Fjord Valley - Jones, Eleanor L.; Hodson, Andrew J.; Thornton, Steven F.; Redeker, Kelly R.; Rogers, Jade; Wynn, Peter M.; Dixon, Timothy J.; Bottrell, Simon H.; O’Neill, H. Brendan (Frontiers in Earth Science, 2020)
Warming of ground is causing microbial decomposition of previously frozen sedimentary organic carbon in Arctic permafrost. However, the heterogeneity of the permafrost landscape and its hydrological processes result in different biogeochemical processes across relatively small scales, with implications for predicting the timing and magnitude of permafrost carbon emissions. The biogeochemical processes of iron- and sulfate-reduction produce carbon dioxide and suppress methanogenesis. Hence, in this study, the biogeochemical processes occurring in the active layer and permafrost of a high Arctic fjord valley in Svalbard are identified from the geochemical and stable isotope analysis of aqueous and particulate fractions in sediment cores collected from ice-wedge polygons with contrasting water content. In the drier polygons, only a small concentration of organic carbon (< 5.40 dry weight %) has accumulated. Sediment cores from these drier polygons have aqueous and solid phase chemistries that imply sulfide oxidation coupled to carbonate and silicate dissolution, leading to high concentrations of aqueous iron and sulfate in the pore water profiles. These results are corroborated by 34S and 18O values of sulfate in active layer pore waters, which indicate the oxidative weathering of sedimentary pyrite utilising either oxygen or ferric iron as oxidising agents. Conversely, in the sediments of the consistently water-saturated polygons, which contain a high content of organic carbon (up to 45 dry weight %), the formation of pyrite and siderite occurred via the reduction of iron and sulfate. 34S and 18O values of sulfate in active layer pore waters from these water-saturated polygons display a strong positive correlation (R2 = 0.98), supporting the importance of sulfate reduction in removing sulfate from the pore water. The significant contrast in the dominant biogeochemical processes between the water-saturated and drier polygons indicates that small-scale hydrological variability between polygons induces large differences in the concentration of organic carbon and in the cycling of iron and sulfur, with ramifications for the decomposition pathway of organic carbon in permafrost environments.